2012
DOI: 10.4049/jimmunol.1200342
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Autoimmunity in the Absence of IL-2 Is Driven by Uncontrolled Dendritic Cells

Abstract: BALB/c IL-2–deficient (IL-2–KO) mice develop systemic autoimmunity, dying within 3 to 5 wk from complications of autoimmune hemolytic anemia. Disease in these mice is Th1 mediated, and IFN-γ production is required for early autoimmunity. In this study, we show that dendritic cells (DCs) are required for optimal IFN-γ production by T cells in the IL-2–KO mouse. Disease is marked by DC accumulation, activation, and elevated production of Th1-inducing cytokines. IL-2–KO DCs induce heightened proliferation and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…Although IL-2 has not been considered as a modulatory factor for DCs in this study, the enhanced DC expression of co-stimulatory molecules observed with CD4 + T cell transfer into RAG −/− hosts did not seem to require the activity of IL-2—presumably produced from CD4 + T cells transferred—on DCs with mainly two reasons: First, the enhancement of CD80 and CD86 expression on DCs in RAG −/− mice was not detected with in vivo administration of IL-2 delivered as a form of IL-2 and anti-IL-2 immune complexes ( 19 ), for which we also confirmed in our study (data not shown). Second, similar to the results observed with CD4 + T cell transfer into RAG −/− hosts, the enhanced expression of DC costimulatory molecules has also been reported in mice lacking IL-2 or its receptors (CD25 and CD122), which is known to be accompanied by spontaneous activation of conventional CD4 + CD25 − T cells resulting from the lack of Treg suppression in these mice ( 48 ). Hence, although we favor the view that IL-2 is dispensable for inducing the enhanced DC expression of co-stimulatory molecules, the additional experiments—e.g., using adoptive transfer with CD25- or CD122-deficient OT-I cells into RAG −/− hosts—will be necessary to provide strong evidence for a direct stimulatory role of IL-2 on CD8 + T cells.…”
Section: Discussionsupporting
confidence: 67%
“…Although IL-2 has not been considered as a modulatory factor for DCs in this study, the enhanced DC expression of co-stimulatory molecules observed with CD4 + T cell transfer into RAG −/− hosts did not seem to require the activity of IL-2—presumably produced from CD4 + T cells transferred—on DCs with mainly two reasons: First, the enhancement of CD80 and CD86 expression on DCs in RAG −/− mice was not detected with in vivo administration of IL-2 delivered as a form of IL-2 and anti-IL-2 immune complexes ( 19 ), for which we also confirmed in our study (data not shown). Second, similar to the results observed with CD4 + T cell transfer into RAG −/− hosts, the enhanced expression of DC costimulatory molecules has also been reported in mice lacking IL-2 or its receptors (CD25 and CD122), which is known to be accompanied by spontaneous activation of conventional CD4 + CD25 − T cells resulting from the lack of Treg suppression in these mice ( 48 ). Hence, although we favor the view that IL-2 is dispensable for inducing the enhanced DC expression of co-stimulatory molecules, the additional experiments—e.g., using adoptive transfer with CD25- or CD122-deficient OT-I cells into RAG −/− hosts—will be necessary to provide strong evidence for a direct stimulatory role of IL-2 on CD8 + T cells.…”
Section: Discussionsupporting
confidence: 67%
“…To analyze the role of Tfh and Tfr cells in the IL-2 KO, we obtained IL-2 KO mice on the C57BL/6 (B6) background because this strain was genetically compatible with most conditional KO strains that are also on the B6 background. We found that IL-2 KO mice on the B6 background in our facility were healthier than reported for IL-2 KO mice on the BALB/c background (38,39,43). In our colony, most B6 IL-2 KO mice live longer than 5 wk and have a lifespan more similar to what was seen with IL-2 KO mice on the mixed 129-O1a 3 C57BL/6 background (37,38).…”
Section: Tfh Cells But Not Tfr Cells Are Increased In the Absence Of supporting
confidence: 45%
“…Cardiac punctures or eye bleeds were performed immediately following cervical dislocation, and blood collected in heparinized tubes (28). Complete blood counts were evaluated within 24 hours on a Hemavet 950 Veterinary Hematology System.…”
Section: Methodsmentioning
confidence: 99%